Use of virginiamycin improves performance of high-prolific sows during gestation and lactation over two cycles (Research, Society and Development, 2021)
Feed additives can be used as potential strategies to enhance the efficiency of nutrient utilization by the sow can impact on the reduction of feed costs and in addition improve sow and litter health. The objective of this study was to evaluate the impact of the supplementation of virginiamycin (VM) in diets for gestating and lactating sows over two consecutive productive cycles on the animals productive and reproductive performance. Sows that received VM showed a lower BW, body protein and energy losses during both lactations when compared to control sows (P = 0.001). VM treatment increased (+6%; P = 0.001) piglet weaning weight. The litter daily gain was also influenced (P = 0.001) by the treatments were litters from VM fed sows showed an improved daily gain when compared to control sows (2.61 vs. 2.24 kg d-1 respectively). Average daily milk production improved by 17% (P = 0.001) in the VM sows when compared with the control. Also, an improvement in milk fatty acid profiles were found in sows fed VM. As a conclusion, we can infer that the constant use of VM in the diets of sows during gestation and lactation improves both sow and litter performance.